ChemInform Abstract: Redox‐Neutral Iron—Sulfur Promoted Transformation of 2‐Nitrophenols and 2, 6‐Disubstituted p‐Cresols into 2‐Arylbenzoxazoles. Issue 51 (23rd December 2014) - Saibara, Masahiko; Ashida, Kazuhito; Satomi, Kouji; Iwai, Toshiyuki; Nakai, Takeo; Mihara, Masatoshi; Ito, Takatoshi; Mizuno, Takumi
Abstract Substitution of 2, 6‐di‐tert‐butyl‐p‐cresol (II) by 2‐tert‐butyl‐p‐cresol, 2, 6‐dimethoxy‐p‐cresol or 1‐tert‐butyl‐toluene results in the isolation of the corresponding products in small or trace amounts only.